Uma comparação do custo computacional dos emparelhamentos bilineares Ate, R-Ate e Optimal Ate sobre curvas Barreto-Naehrig - Sangalli, Leandro Aparecido; Henriques, Marco Aurélio Amaral (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2015)
This work presents a detailed theoretical evaluation and compares the computational costs of Ate, R-Ate and Optimal Ate bilinear pairings defined over Barreto-Naehrig curves. The evaluation confirmed some experimental results present in the literature, showing a slightly better performance (around 0, 5%) of R-Ate pairings over Optimal Ate. Moreover, a virtual generic processor, with a restricted instruction set, was used to measure and compare the costs of the mentioned pairings under different conditions, such as different word sizes (including 128 and 256 bits), different multipliers and different coordinates. The change in word size was found to have the largest impact in the pairings computational costs when compared to other parameters.